Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $(X,\mu)$ be a measure space. Suppose that $0 < p_{0} < p < p_{1} < \infty$ and $\frac{1}{p} = \frac{1-\theta}{p_{0}} + \frac{\theta}{p_{1}}$ for some $\theta \in (0,1)$. If $f \in L^{p_{0},\infty}(X,\mu) \cap L^{p_{1},\infty}(X,\mu)$, then $f \in L^{p,\infty}(X,\mu)$ and $$\left\|f\right\|_{L^{p,\infty}} \leq \left\|f\right\|_{L^{p_{0},\infty}}^{1-\theta}\left\|f\right\|_{L^{p_{1},\infty}}^{\theta}$$ It isn't hard to show this inequality for a constant greater than 1, using Holder's inequality for $L^{p,\infty}$ spaces (Grafakos Classical Fourier Analysis Exercise 1.1.15), but I can't figure out how to prove the stated inequality.

share|cite|improve this question
Where is $p_1$? $0 < p_0 < p < p_1$? – Jonas Teuwen Jul 28 '11 at 20:15
It is late, but are you sure it is true? Let $f = 2 1_A$. Then $\|f\|_{p, \infty} = \mu(A)^{1/p}$. Hence we get $\mu(A)^{1/p} \leq \mu(A)$. Did I make a mistake somewhere? If not, this fails for $p = \frac12$ and $\mu(A) = 2$. – Jonas Teuwen Jul 28 '11 at 22:30
I'm not sure that the stated inequality is true, although Grafakos appears to claim that it's true by including it in his book. However, I don't understand how you get $\mu(A)^{\frac{1}{p}} \leq \mu(A)$. Don't we have $\left\|f\right\|_{L^{p_{0},\infty}} = \mu(A)^{\frac{1}{p_{0}}}$ and $\left\|f\right\|_{L^{p_{1},\infty}} = \mu(A)^{\frac{1}{p_{1}}}$. Hence, $$\left\|f\right\|_{L^{p_{0},\infty}}^{1-\theta}\left\|f\right\|_{L^{p_{1},\inft‌​y}}^{\theta} = \mu(A)^{\frac{1}{p}}$$ – Matt Rosenzweig Jul 28 '11 at 23:49
Right, I was mistaken (the sum is $1/p$ not $1$). I will see if I can find a solution, part a) was easy (I have done it some years ago) but with the Hölder inequality for weak $L^p$ you get an additional constant... – Jonas Teuwen Jul 29 '11 at 12:25
up vote 7 down vote accepted

WLOG assume $f \geq 0$.

$$ \|f\|_{p,\infty}^p := \sup_{t > 0} t^p \mu\{ f > t\} $$

Now, fix $\lambda,\eta \in (0,1)$, you have

$$ t^p \mu\{ f > t\} = t^{\eta p} \left(\mu\{f > t\}\right)^\lambda \cdot t^{(1-\eta)p}\left( \mu\{f > t\}\right)^{(1-\lambda)} $$


$$ = \left( t^{\eta p / \lambda} \mu\{f > t\}\right)^{\lambda} \cdot \left( t^{(1-\eta) p /(1-\lambda)} \mu\{f > t\}\right)^{1-\lambda} $$

so taking the sup of the terms inside the parentheses

$$ \| f \|_{p,\infty}^p \leq \| f \|_{\eta p/\lambda,\infty}^{\frac{\eta p}{\lambda}\cdot\lambda}\| f\|_{(1-\eta)p/(1-\lambda),\infty}^{\frac{(1-\eta)p}{1-\lambda}\cdot(1-\lambda)} $$


$$ \| f \|_{p,\infty} \leq \| f \|_{\eta p / \lambda,\infty}^\eta \| f \|_{(1-\eta)p/(1-\lambda),\infty}^{1-\eta} $$

Now let $p_0 = \eta p / \lambda$ and $p_1 = (1-\eta)p / (1-\lambda)$. It is simple to check that

$$ \frac{\eta}{p_0} + \frac{1-\eta}{p_1} = \frac{\lambda}{p} + \frac{1-\lambda}{p} = \frac{1}{p} $$

share|cite|improve this answer
Hah, it's that easy. Nice +1. – Jonas Teuwen Jul 29 '11 at 15:52
@Jonas: The natural next question to ask is what can be said about general Lorentz spaces $L^{p,s}$. Using the same method you can prove something that allows to interpolate both in $p$ and in $s$, but I am not sure what the constant should be. – Willie Wong Jul 29 '11 at 16:20
@Willie: Many Thanks! – Matt Rosenzweig Jul 29 '11 at 19:15

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.